Therapeutic Suggestions for Chronic Subdural Hematoma Associated with Idiopathic Thrombocytopenic Purpura: A Case Report and Literature Review - Takase, Hajime (NMC Case Rep J, 2015)
A 66-year-old woman who was previously diagnosed with idiopathic thrombocytopenic purpura (ITP) presented with mild right-sided hemiparesis and drowsiness. Head computed tomography (CT) imaging demonstrated a massive left chronic subdural hematoma (CSDH) with a midline shift. Because initial laboratory data showed a significantly decreased blood platelet count (0.3 × 10(4)/mm(3)), medical treatments such as platelet transfusion, intravenous immunoglobulin (IVIG), and high-dose corticosteroid therapy, were initiated. She clinically and radiologically responded well to these treatments without any surgical intervention. In addition to presenting our case, we searched the PubMed and Ichushi Web databases to comprehensively illustrate clinical characteristics and treatment outcomes of similar cases. Including the present case, we found 19 reports and 23 cases of CSDH associated with ITP in the literature, and assessed 17 reports and 21 cases that were written in English and Japanese. None or mild neurological symptom were seen in 13 cases, and severe, such as coma and hemiparesis, were described in the younger 8 cases with significant difference. All except one were first treated with medical therapies. Most cases of the former group responded well to conservative therapy. On the other hand, most in the latter eventually needed surgical treatment in addition except recent two cases including the present case. CSDH associated with ITP is rarely described, and its management remains controversial. However, this report highlights multiple continuous medical treatments under strict observation and general care might be a useful alternative to avoid surgery in cases presenting with severe neurological deficits and extremely low platelet counts.